COMMUNAL COMMUNITY READING ON SURAH AL WAQIAH (STUDY OF AL-QURAN RECEPTION IN PP AL MAWADDAH WARRAHMAH KOLAKA) - Nasution Zakariah, Abdul Haris; Abubakar, Achmad; Firdaus, Firdaus; Abunawas, Kamaluddin (Jurnal Diskursus Islam, 2020)
Pondok Pesantren Al Mawaddah Warrahmah Kolaka since its inception in 1998. Aims to form a generation of Qurani. During its development, efforts were made to achieve this goal, one of which was to form a tradition of reciting the chosen surah of the Koran after performing obligatory prayers and sunnah, including recitation of surah al-waqiah after performing the Fajr prayer. By using the theory of social construction of reality offered by Peter L. Berger and Thomas Luckmaan in the form of externalization, objectification and internalization phases. The research shows that the reading of the communal pesantren towards surah al-waqiah emits several social meanings, namely: obedience to the Kiai and the rules of the boarding school, expecting blessings from reading the Koran, getting fadhilah from the recited surah, and as mediation in tahsin and tahfiz. on the surah of the Koran that is read.